(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The commodity market poses a variety of risks which can all greatly influence trade profits and therefore need to be monitored and managed. The high volatility of the market creates uncertainty about future prices and thus poses a significant threat. The Commodity Market is a complex industry where raw materials are traded on a regulated exchange. In India, it is only in the last decade that commodity futures exchanges have been actively encouraged after the set-up of national level exchanges witnessed exponential growth in trading with the turnover increasing from 5.71 lakh crores in 2004-05 to 52.48 lakh crores in 2014-15. Commodity price risk management is important for stabilising incomes of corporate, individuals (especially farmers) and the economy. Commodity prices are considered as the main source of market risk and are used to be the main consideration for most of the organisation engaged with commodity market.